Sport activity of polish runners and the resulting marketing potential - Waśkowski, Zygmunt; Jasiulewicz, Anna (Journal of Education, Health and Sport, 2017)
The purpose of this article is to analyze the sport activity of runners and to estimate on this basis their marketing potential in cross-industry. The prepared publication is therefore empirical-cognitive, resulting in the identification of the behavior and the determinants of purchase decisions made by the sports-active persons. The empirical part of the paper was prepared on the basis of one survey conducted twice by one of the authors, on the sample of several thousand runners. The outcomes were confronted with the available results of other studies conducted in recent years on the Polish sports market. The results of the research concerning issues such as attitude towards running, the importance of this activity in life, the role and importance of information sources, the frequency and place of purchases show the high heterogeneity of behavior of Polish runners. Based on the empirical evidence it may be observed that marketing potential of this market segment from the vendor point of view is very promising.